2018
DOI: 10.1177/0363546518808033
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Capsular Plication in Patients With Labral Tears and Borderline Dysplasia of the Hip: Analysis of Risk Factors for Failure

Abstract: Background: Hip arthroscopy for the treatment of instability in the setting of borderline dysplasia is controversial. Capsular management in such cases is an important consideration, and plication has been described as a reliable technique, with good midterm outcomes reported when indications are appropriate. Hypothesis: Patients with borderline dysplasia who have a lower lateral center-edge angle (LCEA) and greater age will be at a higher risk of failure after arthroscopic capsular plication. Study Design: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 44 publications
1
80
0
Order By: Relevance
“…In addition, all procedures were performed by a single surgeon, which may limit the generalizability of the results. Furthermore, capsular and labral management has evolved in the recent years and in consequence, patients who underwent labral debridement and capsular release in the ongoing study would currently be treated with labral restoration technique such labral reconstruction or labral augmentation, and capsular plication (23,24,(44)(45)(46). ConclusionRegardless of the level of participation, tennis players who underwent hip arthroscopic surgery reported statistically significant PRO improvements.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, all procedures were performed by a single surgeon, which may limit the generalizability of the results. Furthermore, capsular and labral management has evolved in the recent years and in consequence, patients who underwent labral debridement and capsular release in the ongoing study would currently be treated with labral restoration technique such labral reconstruction or labral augmentation, and capsular plication (23,24,(44)(45)(46). ConclusionRegardless of the level of participation, tennis players who underwent hip arthroscopic surgery reported statistically significant PRO improvements.…”
mentioning
confidence: 89%
“…(23) The decision to release, repair, or plicate the capsule was dictated by the patient's Beightons score and acetabular coverage. (24,25) Rehabilitation Using a fitted X-Act ROM brace (DJO Global Vista, CA) and crutches, patients were instructed to use toe-touch weight bearing for two weeks. To restore strength and range of motion, physical therapy was initiated one day after surgery.…”
Section: Surgical Techniquementioning
confidence: 99%
“…If there is joint instability present as indicated by preoperative and intraoperative criteria 28,29 capsular plication is performed. If no joint instability is present, capsulorrhaphy is performed.…”
Section: Capsular Managementmentioning
confidence: 99%
“…This is especially relevant to hips with so-called "borderline dysplasia," in which hip arthroscopy is being reported as an effective treatment solution. 6 But what qualifies as borderline dysplasia on plain radiographs? A recent systematic review by Yeung et al 7 showed that there is a wide range in LCEA when defining borderline dysplasia ranging from 18 to 25 with overlap, with moderate dysplasia ranging from 16 to 24 .…”
Section: Why Is Defining the Severity Of Acetabularmentioning
confidence: 99%